COMPARATIVE ACCOUNT OF GROWTH RATE OF BODY PARTS WITH TOTAL LENGTH IN RITA PAVIMENTATA (GUNTHER) - QURESHI, T. A.; TIWARI, V. K. (Journal of Indian Fisheries Association, 2015)
The paper deals with sex-wise growth rate of different body parts in relation to total length in Rita pavimentata (Gunther). Growth rates calculated on pooled dat by using the common regression coefficient ’b’ reveals isometric and homogeneous nature in sexes. Keywords : Rita, isometric, regression, Narmada, India